NEURAL TENSION DYSFUNCTION LEVEL IN THE LOWER LIMBS AND SHORT HAMSTRING SYNDROME - Negara, Anak Agung Gede Angga Puspa; Antari, Ni Komang Ayu Juni; Kinandana, Gede Parta (Sport and Fitness Journal; Vol 11 No 2 (2023): Volume 11, No.2, May 2023, 2023)
Hamstring muscles play a role in several functional human movements such as walking, running, and jumping. Changes in hamstring extensibility can cause joint dysfunction and have been associated with several orthopedic disorders, such as low back pain and patellofemoral syndrome. Previous studies have revealed changes in individual tolerance to stretching rather than changes in muscle structure in short hamstring syndrome (SHS). In addition, it is believed that the strong afferent input from stretching can reduce the impulse rate of mechanoreceptors and proprioceptors which can also influence sensory adaptation. Reduced ROM in short hamstring syndrome is also caused by neural tension dysfunction. This study aimed to describe the relationship between the incidence of neural tension dysfunction and indications of the occurrence of SHS in a healthy population and how neurodynamic stretching (NDS) interventions can effectively increase hamstring flexibility. The research method used was a literature study of articles using secondary data in the form of a review of research journals related to the relationship between neural tension dysfunction and SHS. Previous studies have shown that interventions aimed at neural structures such as administering neurodynamic stretching are more effective when compared to other intervention approaches in increasing flexibility in SHS. This is due to changes in the nervous structure such as the ability of the nerves to accept tension loading that accompanies changes in the length of the hamstring muscles on the SHS. In addition, increased mechanosensitive due to neural tension dysfunction is one of the main factors in the limitation of motion in SHS. Based on the literature review, it can be concluded that: there is a relationship between neural tension dysfunction in the lower limbs and the incidence of short hamstring syndrome in a healthy population.